Peranan Tuan Guru Abdul Basit Bin Mahmud dalam Memperkasa Tradisi Keilmuan dan Pengajian Pondok di Selatan Thailand - Abdulloh Salaeh; Amran Abdul Halim; Adnan Mohamed Yusoff; Nidzamuddin Zakaria; Walid Mohd Said; Syed Najihuddin Syed Hassan (Academic Inspired Network, 2026)
Tier 3